Zn1−xFexO films: from transparent Fe-diluted ZnO wurtzite to magnetic Zn-diluted Fe3O4 spinel. Issue 42 (7th October 2015) - Perrière, J.; Hebert, C.; Nistor, M.; Millon, E.; Ganem, J. J.; Jedrecy, N.
Abstract : The resistivity of the Zn1− x Fe x O thin films drastically depends upon the nature of the phases which are present, i.e. highly resistive Fe-doped ZnO wurtzite and half-metallic Zn-doped Fe3 O4 spinel. Abstract : The different phases formed in Zn1− x Fe x O thin films where x varies from 0 to 1, as well as their structural characteristics and physical properties, have been investigated. In particular, the interrelationships between the iron concentration, the oxygen composition and the microstructure of the films have been determined. The Zn1− x Fe x O films were grown on c-cut sapphire substrates by pulsed-laser deposition. For 0 < x < 0.35, epitaxial films with a wurtzite (ZnO like) structure were obtained, while for 0.65 < x < 1, spinel (Fe3 O4 like) epitaxial films were observed. In the intermediate region (0.35 < x < 0.65) the phase separation of the Zn1− x Fe x O films leads to the formation of both wurtzite and spinel phases. Whatever is the x value, the films display well-defined in-plane epitaxial relationships between the wurtzite (or spinel) phase and the substrate. The optical, electrical and magnetic properties of the Zn1− x Fe x O films are discussed in relation with their structural characteristics.